Pengaruh Likuiditas, Profitabilitas dan Ukuran Perusahaan Terhadap Harga Saham Pada Perushaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia - Hasibuan, Nuricha Putri; Salim, Muhammad Agus; Wahono, Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This research aims to determine the effect of profitability liquidity and company size on share prices in food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The population of this study uses food and beverage companies listed on the Indonesia Stock Exchange for the 2020-2022 period. The sampling method used purposive sampling, which resulted in a sample of 84 food and beverage companies. The data analysis method used consists of the classic assumption test, multiple linear regression analysis, t test, and coefficient of determination test. The results of this research show that liquidity has a significant effect on share prices, profitability does not have a significant effect on share prices and company size does not have a significant effect on share prices. Keywords: Liquidity, Profitability, Company Size, and Share Price